O2-S5.03 Sex, drugs and structural interventions: unstable housing associated with increased HIV risk behaviour in a cohort of people on treatment in British Columbia, Canada. (10th July 2011) - Parashar, S; Palmer, A; O'Brien, N; Chan, K; Milan, D; Samji, H; Montaner, J; Hogg, R
Abstract : Background: Unstable living conditions may increase risk for HIV exposure and transmission. This analysis examines housing as a structural factor associated with drug and sexual risk behaviours among individuals accessing antiretroviral treatment (ART). We hypothesised that unstable housing is significantly associated with sex exchange and recent injection drug use (IDU). Methods: The LISA cohort is a cross-sectional study of individuals on ART in British Columbia. Interviewer-administered surveys collect information regarding housing, drug use, utilisation of health services and other clinically relevant socio-demographic factors. Clinical variables, such as CD4 count and viral load, were obtained through longitudinal linkages with the Drug Treatment Program (DTP) at the BC Centre for Excellence in HIV/AIDS. In order to examine the effect of housing status on HIV risk behaviour, multivariate logistic regression was used with three outcomes: sex exchange, unprotected intercourse and recent IDU. Results: Between 2007 and 2010 approximately 1000 participants were interviewed. The survey was modified part way through the study to stratify sexual behaviour based on partner-type. This analysis is thus restricted to 477 interviews with full information on all outcomes. Median age was 45 (IQR=39–51) and 29.8% (142) were female. After adjusting for potential confounders, unstable housing was significantly associated with a history of exchanging sex for food, money or drugs (Adjusted OR [AOR]=1.92; 95% CI=1.11% to 3.33%) and recent IDU (AOR=2.39; 95% CI=1.41% to 4.03%). Unprotected sexual intercourse with regular partners, casual contacts and clients, was not significantly associated with housing status. Conclusion: Greater levels of sexual exchange and injection drug use among unstably housed populations are associated with aspects of transient living conditions, as well as the increased need and opportunity for sexual exchanges for food, shelter, drugs and money. Our findings suggest that secure and affordable housing is an important structural intervention that may reduce HIV risk behaviour.